The Relationship Between Peer Conformity and the Tendency of Cyberbullying Among High School Students in Yogyakarta (Journal of Social And Education Research, 2023)
Adolescence is a transitional phase toward adulthood, characterized by physical, psychological, cognitive, and social changes. During this period, adolescents often experience conflicts, particularly within peer environments, which may arise due to competition, provocation, or misunderstandings. One common form of conflict in this era is cyberbullying, in which perpetrators use electronic media to carry out their actions. A significant factor influencing this phenomenon is peer conformity. Close relationships among peers encourage adolescents to adjust their attitudes and behaviors to gain acceptance within their groups, thereby increasing their social and psychological needs. This study aimed to examine the relationship between peer conformity and cyberbullying among high school students in Yogyakarta. A quantitative method with a correlational approach was employed, involving 116 respondents selected through purposive sampling. Data were collected using scales and analyzed using Pearson Product Moment correlation. The results indicated that most respondents had low levels of cyberbullying (81.0%) and low peer conformity (71.6%). Analysis revealed a significant positive relationship (p = 0.000; r = 0.778), suggesting that higher peer conformity is associated with higher motivation for cyberbullying. It is recommended that adolescents be selective in choosing peer groups that support positive behaviors